An outline of the inshore submarine geology of Southern South West Africa and Namaqualand - O'Shea, Desmond O'Connor (Department of Geological Sciences, 2016)
An outline of the inshore submarine geology of the south western coast of southern Africa is presented. The study is derived from diamond prospecting operations carried out between 1964 and 1970 in the shallow waters between Walvis Bay in South West Africa and the Olifants River mouth in Namaqualand, Republic of South Africa - a distance of approximately 1 000 km (600 miles). The area can be conveniently subdivided into three regions from north to south: (i) Tidal Diamond's Concession (T.D.C.) from Sandwich Harbour to Hottentot Bay. (ii) Marine Diamond Corporation's Concession (M.D.C.) from Luderitz to the mouth of the Orange River. (iii) Southern Diamond's Concession (S.D.C.) from the Orange River mouth to the mouth of the Olifants River.